ADDRESSING GLOBAL TAX AVOIDANCE AND TAX EVASION IN INDONESIA - Yudisatria, Aria (Journal of Tax Law and Policy, 2024)
Globalisation has significantly reshaped the global economy, enabling the seamless movement of capital, resources, and information across borders. While this transformation has brought economic benefits, it has also facilitated aggressive tax avoidance and evasion by multinational enterprises (MNEs) and individuals. These actors exploit international tax loopholes, shifting profits to tax havens to minimise tax liabilities. In Indonesia, this phenomenon poses a serious challenge, leading to substantial revenue losses that impact economic development and social welfare. This research examines the relationship between globalisation and tax avoidance, focusing on the Indonesian context. It explores the role of global tax governance and the implementation of a smart regulation framework as potential solutions. The study argues that an inclusive global tax governance system and a responsive regulatory tax regime through smart regulation are crucial to effectively addressing aggressive tax avoidance and evasion in Indonesia.